Implikatur Percakapan pada Film Air Mata di Ujung Sajadah Karya Titien Wattimena - Agustin, Dyan Reza; Pebrianti, Ike Tri; Nopriani, Henny (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
The formulation of the problem in this study is how is the conversational implicature in the movie “Air Mata di Ujung Sajadah” by Titien Wattimena? The purpose of this study is to describe the conversational implicature in the movie “Air Mata di Ujung Sajadah” by Titien Wattimena. The researcher used a qualitative method to understand the linguistic phenomenon under study. Therefore, qualitative analysis concentrates on determining meaning, explanation, clarification, and placing data in their respective contexts, often presenting data in the form of words rather than numbers. The research methodology also includes research materials, tools, research lines, variables, and data to be collected.Researchers found conversational implicature in the film Air Mata di Ujung Sajadah by Titien Wattimena with a total of 69 (sixty nine) with general conversational implicature 16 (sixteen) scaled implicature 11 (eleven) special conversational implicature 33 (thirty three) and conventional implicature 9 (nine). Based on the results of data analysis, the researcher found that special conversational implicature is the most dominant in this study.